2021
DOI: 10.3233/jad-201015
|View full text |Cite
|
Sign up to set email alerts
|

Partial Inhibition of Mitochondrial Complex I Reduces Tau Pathology and Improves Energy Homeostasis and Synaptic Function in 3xTg-AD Mice

Abstract: Background: Accumulation of hyperphosphorylated tau (pTau) protein is associated with synaptic dysfunction in Alzheimer’s disease (AD). We previously demonstrated that neuroprotection in familial mouse models of AD could be achieved by targeting mitochondria complex I (MCI) and activating the adaptive stress response. Efficacy of this strategy on pTau-related pathology remained unknown. Objective: To investigate the effect of specific MCI inhibitor tricyclic pyrone compound CP2 on levels of human pTau, memory … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 97 publications
3
35
0
Order By: Relevance
“…While APP/PS1 mice utilized in our study do not have pTau accumulation, increased levels of Sirt3 and decreased activity of GSK3β suggest that CP2 treatment could also be effective in reducing Tau toxicity. Indeed, our independent study in the mouse model of AD that along with the mutant human APP and PS1 proteins also expresses mutant human Tau protein, the 3xTg-AD mice 70 , demonstrated that chronic CP2 treatment reduced pTau levels and improved LTP and energy homeostasis in symptomatic male and female mice. While this study interrogated CP2 efficacy only in female APP/ PS1 mice, treatment in 3xTg-AD mice was beneficial in males and females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While APP/PS1 mice utilized in our study do not have pTau accumulation, increased levels of Sirt3 and decreased activity of GSK3β suggest that CP2 treatment could also be effective in reducing Tau toxicity. Indeed, our independent study in the mouse model of AD that along with the mutant human APP and PS1 proteins also expresses mutant human Tau protein, the 3xTg-AD mice 70 , demonstrated that chronic CP2 treatment reduced pTau levels and improved LTP and energy homeostasis in symptomatic male and female mice. While this study interrogated CP2 efficacy only in female APP/ PS1 mice, treatment in 3xTg-AD mice was beneficial in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Following 24 h fixation, samples were processed using the following protocol based on the serial block-face method developed by the National Center for Microscopy and Imaging Research (La Jolla, CA; https://ncmir.ucsd. edu/sbem-protocol): (1) (14) dehydrated through ethanol series (60,70,80,95, 100, 100%) 10 min each, (15) two rinses in 100% acetone 10 min each, (16) resin 1:2, 1:1, 3:1 in acetone 0.5 h, 1 h, 2 h, overnight in 100% resin. Samples were embedded into the Durcapan hard resin (EMS, Hatfield, PA), and allowed to polymerize at a minimum of 24 h prior to trimming and mounting.…”
Section: Compound Management 2 Assay Setup 3 Reaction Termination Amentioning
confidence: 99%
“…Further related to metabolic regulation, SIRT3, PGC1 α , TFAM, GLUT3, and GLUT4 were increased and phospho-PDH:total PDH ratio was decreased 24 h after gavage of CP2 at 25 mg/kg in APP/PS1 mice 274 . Chronic administration (2–14.5 months) improved cognition in the APP/PS1 and 3xTg mouse models of AD and decreased amyloid plaques in APP/PS1 mice after 4 months 272 , 273 , 274 , 275 .…”
Section: Targeting Mitochondrial Bioenergetics and Mitochondrial Qual...mentioning
confidence: 98%
“…The authors suggested a deregulation of glucose uptake in 3xTg-AD mice that becomes more prominent with age. Another study also reported a significant reduction in cerebral glucose uptake in 16-month-old 3xTg-AD male and female mice compared to WT, with more prominent differences for females [ 122 ].…”
Section: Neuroimaging Of Mouse Models Of Admentioning
confidence: 99%